2010
DOI: 10.1051/0004-6361/200913182
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of infrared luminosity functions of galaxies in the AKARI NEP-deep field

Abstract: Aims. Dust-obscured star-formation increases with increasing intensity and increasing redshift. We aim to reveal the cosmic starformation history obscured by dust using deep infrared observation with AKARI. Methods. We constructed restframe 8 μm, 12 μm, and total infrared (TIR) luminosity functions (LFs) at 0.15 < z < 2.2 using 4128 infrared sources in the AKARI NEP-deep field. A continuous filter coverage in the mid-IR wavelength (2.4, 3.2, 4.1, 7, 9, 11, 15, 18, and 24 μm) by the AKARI satellite allowed us … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 65 publications
9
97
0
Order By: Relevance
“…Here, we present the recent determination of mid-IR (8 µm and 12 µm) luminosity functions for local http://pkas.kas.org (z < 0.3) galaxies based on the multi-band data from the NEP-Wide point source catalogue covering from optical u * band to AKARI 24 µm band together with spectroscopic redshift data for selected sample. This work complements the results from the NEP-Deep Survey (Goto et al, 2010), which derived LFs for more distant universe (z > 0.3).…”
Section: The Nep-wide Datasupporting
confidence: 78%
“…Here, we present the recent determination of mid-IR (8 µm and 12 µm) luminosity functions for local http://pkas.kas.org (z < 0.3) galaxies based on the multi-band data from the NEP-Wide point source catalogue covering from optical u * band to AKARI 24 µm band together with spectroscopic redshift data for selected sample. This work complements the results from the NEP-Deep Survey (Goto et al, 2010), which derived LFs for more distant universe (z > 0.3).…”
Section: The Nep-wide Datasupporting
confidence: 78%
“…In their work, ∼20 000 objects were detected in the near-infrared (NIR) bands, while 7300 objects were detected in the MIR bands. Using these catalogues, Takagi et al (2010) 1 found LIRGs with unusually bright emission from PAH, and Goto et al (2010) evaluated the luminosity function without associated uncertainties from the K-correction. However, the original catalogue leaves room for improvement, especially in the image analysis stage, because most of the images are contaminated by scattered light from inside the detector, stray light from the Earth limb, artificial sources due to bright objects, and patterns from the optical system.…”
Section: Introductionmentioning
confidence: 99%
“…Pérez-González et al 2005;Le Floc'h et al 2005;Babbedge et al 2006;Caputi et al 2007;Goto et al 2010). However, this work can suffer uncertainty from the k-correction, which requires knowing the appropriate mid-IR spectral energy distribution (SED).…”
Section: Introductionmentioning
confidence: 99%